Physicochemical properties and bioavailability of bio-calcium products from tilapia bone: A comparative study with synthetic hydroxyapatite - Arkanit, Kornpaka; Senphan, Theeraphol; Issapap, Nursakich; Mungmueang, Natthapong; Sriket, Pornpimol; Benjakul, Soottawat; Sriket, Chodsana (My University, 2025)
This study compared three calcium products derived from tilapia bones (fish bone powder, bio-calcium, and calcined bone) with synthetic hydroxyapatite as a reference material. The chemical compositions, physical properties, and calcium bioavailability were analyzed. The yield percentage decreased from 44.4 % in fish bone powder to 27.4 % in bio-calcium. The yield percentage then increased to 64.9 % in calcined bone. Synthetic hydroxyapatite showed 100 % yield. The ash content increased progressively from 68.5 % to 99.4 %. The calcium content increased from 18.9 % to 31 %, with Ca/P ratios improving from 3.3 to 1.7, approaching the ideal ratio of natural bone mineral (1.67). Heavy metals were not detected in any samples. All products exhibited high whiteness values (L∗ 91.8–95.0). Water activity values ranged from 0.33 to 0.50. The median particle sizes varied between 17.39 and 31.05 μm. Lipid oxidation decreased through the processing stages. Calcium bioavailability was the highest in synthetic hydroxyapatite (5.4 %). Bio-calcium showed 4.1 % bioavailability. The products demonstrated potential for food fortification and biomedical applications. The findings support the use of tilapia bones as a sustainable source of calcium production.
Keywords: Bio-calcium; Calcium bioavailability; Fish by-products; Synthetic hydroxyapatite; Tilapia bone